Nutritional Quality, pH, and Sensory Acceptance of Lactobacillus plantarum Soft Cheese - Lola Ayu Istifiani; Widyanto, Rahma Micho; Tsalissavrina, Iva; Irma Sarita Rahmawati; Razinah Sharif; Velisia, Lola Saritama Amarsya; Pineda, Aliyyah Bunga Teratai Putri; Luh Asmi Arisanty Dewi; Aisyah Washfa Muthi’ah (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2026)
The increasing prevalence of non-communicable diseases in Indonesia, especially hypercholesterolemia, has raised awareness of healthy lifestyles and food choices, including probiotic cheese. The development of probiotic cheese is therefore important, especially in terms of nutritional quality, pH, and sensory characteristics. This study aimed to develop probiotic soft cheese using Lactobacillus plantarum FNCC 0026 and to assess its nutritional quality through proximate analysis, pH measurement, and sensory acceptance. A randomized block design was applied with four treatment levels of Lactobacillus plantarum FNCC 0026 (0%, 5%, 10%, and 20%). Nutritional composition was analyzed using proximate methods, pH was measured using a pH meter, and sensory evaluation was conducted under blinded conditions involving 40 panelists. The results showed that starter concentration significantly affected nutritional quality, pH, and sensory properties of probiotic soft cheese. Increasing probiotic levels increased moisture content (55.11±4.02) and pH values (6.50±0.15), while reducing carbohydrate content (1.23±1.48), whereas protein, fat, ash, and energy contents remained relatively stable. Higher probiotic concentrations reduced acceptability in terms of taste, texture, and overall appearance, while moderate concentrations resulted in a more balanced quality and higher consumer acceptance. In conclusion, the 5% Lactobacillus plantarum FNCC 0026 formulation produced the most favorable balance of nutritional quality, pH stability, and sensory acceptance.